Effect of silica fillers on mechanical properties of epoxy/kenaf composites - Jaafar, Che Nor Aiza; Zainol, Ismail; Aremu, Omotoso Oladiran (Institute of Physics Publishing, 2018)
The mechanical properties of epoxy/kenaf composites at various silica content has been investigated. Epoxy resin was mixed with silica filler ranging from 6.7 to 33.3 %w/w before applied into kenaf fibre mat (11.5 %w/w) to fabricate epoxy/silica/kenaf composites using hand layup method. The composites were precured at 80 °C for 2 hour and post cured at 110 °C for 1 hour. The mechanical properties of the composite were analysed using flexural and impact test, meanwhile the surface fracture of the composite was examined by means of scanning electron microscope (SEM). It is found that epoxy/kenaf composite with 20 %w/w silica content exhibited the best mechanical properties, with 3.1 kJ/m2 of impact strength, 44.5 MPa of flexural strength and 2.7 GPa of flexural modulus. Its surface morphology showed the brittle fracture surface with pull out of fibre which indicated poor interaction between epoxy matrix and kenaf fibre.